Nivolumab and Ipilimumab Combination Immunotherapy for Patients with Metastatic Collecting Duct Carcinoma - Tetsuya Danno; Shohei Iwata; Fusako Niimi; Sachi Honda; Haruka Okada; Takeshi Azuma (Case Reports in Urology)
Collecting duct carcinoma (CDC) is a rare, extremely aggressive form of renal cancer. Recently, immune checkpoint inhibitors (ICI), anti-programmed death-1 (PD-1) antibody, and anti-cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) antibody were approved for use against metastatic renal cell carcinoma. We herein described two cases of metastatic renal collecting duct carcinoma treated with a combination immunotherapy consisting of nivolumab and ipilimumab. In the first case, which included a bone metastasis, the best response achieved was stable disease (SD) for one year. In the second case, which was accompanied by a lung metastasis, the best response achieved was a partial response. The outcome of these cases suggested that the combination of nivolumab and ipilimumab is effective against renal collecting duct carcinoma.